The study of the acute and chronic toxicity dipeptide mimetic of brain-derived neurotrophic factor GSB-106 finished dosage form - S. V. Alekseeva; A. V. Sorokina; A. V. Volkova; V. V. Zabrodina; I. A. Miroshkina; K. S. Kachalov; I. V. Alekseev; A. D. Zaharov; P. Yu. Povarnina; A. D. Durnev (Фармакокинетика и Фармакодинамика)
Resume. The study of acute and chronic toxicity of the finished dosage form (SFF) GSB-106, the active substance of which is the substituted dimeric peptide, hexamethylenediamine bis (N-monosuccinyl-L-seryl-L-lysine), which has antidepressant and neuroprotective activity. GSB-106, administered in the maximum allowable volumes and concentrations in a single intragastric and intraperitoneal administration to males and females of outbred white mice in the maximum possible doses, which made up, respectively, 120 mg / kg of the active substance (12 g / kg tablet weight) and 40 mg / kg of active substance (4 g / kg tablet weight) did not cause the death of animals. GSB-106 in doses of 1 mg / kg of the active substance (0.1 g / kg of the tablet mass) and 10 mg / kg of the active substance (1 g / kg of the tablet mass) with daily oral and intragastric administration during the month to females and male rats and rabbits did not affect the recorded integral indicators. The toxic effects of GSB-106 were not observed in clinical, laboratory, pathological and histological studies performed in a generally accepted volume.